1998
DOI: 10.1103/physrevb.57.r3249
|View full text |Cite
|
Sign up to set email alerts
|

Nature of vortex lattice disordering at the onset of the peak effect

Abstract: We report a transport study of the onset of the peak effect in a 2H-NbSe 2 single crystal with very weak pinning. At low driving current, we find that at the onset of the peak effect, where the resistance starts to dip with increasing field, the resistance is hysteretic upon field cycling. The resistance is higher for upward field sweeps than for downward sweeps. The difference between the two has a double-peak feature, indicative of two-stage disordering of a vortex lattice. The resistance hysteresis and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
4
18
0
Order By: Relevance
“…In the past years a lot of work is done in the subject of dynamic transitions of vortex matter when subjected to an applied driving force. [37][38][39][40][41][42][43][44][45][46] Theoretical treatment argues that a static disordered vortex solid could be, dynamically, transformed to a moving solid state ͑that possibly retains crystalline order in some degree͒ under the influence of high driving forces. [38][39][40][41][42] We believe that such a plysical process could be related to the results presented here.…”
Section: Resultsmentioning
confidence: 99%
“…In the past years a lot of work is done in the subject of dynamic transitions of vortex matter when subjected to an applied driving force. [37][38][39][40][41][42][43][44][45][46] Theoretical treatment argues that a static disordered vortex solid could be, dynamically, transformed to a moving solid state ͑that possibly retains crystalline order in some degree͒ under the influence of high driving forces. [38][39][40][41][42] We believe that such a plysical process could be related to the results presented here.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, in disordered samples, it is the static disorder that transforms the vortex lattice into an amorphous vortex solid. This behavior has been observed in the high-T c compounds HgBa 2 CuO 4+δ [18] and YBa 2 Cu 3 O 7−δ [19] and in the low-T c superconductors 2H-NbSe 2 [58,59], CeRu 2 [59] and X 3 Rh 4 Sn 13 [4,57] (X=Ca,Yb). In our case, we observed a sharp drop (∆T ≈ 100 mK) at the end points of the PE which is also hysteretic.…”
Section: Phase Diagram Of Vortex Matter For Nb−2 Comparison With Thementioning
confidence: 89%
“…First, a local peak at T onset , and second a dip at T peak . This is the well-known PE in the critical current J c (the minimum in the measured voltage corresponds to a maximum/peak in the critical current J c ), which was observed in high-T c compounds [4,17,18,51], in superconductors of intermediate-T c as pristine and Carbon-doped MgB 2 [42,52,53], in Nb [9,10,54,55,56] and other low-T c [4,57,58,59] disordered superconductors. The comparison to our magnetic measurements (not shown here) revealed that the PE almost coincides with the upper-critical fields (see fig.…”
Section: Magnetoresistance Measurements and The Peak Effectmentioning
confidence: 99%
“…The discovery of the high temperature superconductors made it relevant to also consider thermal fluctuations as a third energy scale, which lead to melting by suppression of c 66 . This would then yield a peak effect as a precursor of the melting transition [4,5,6].Experimentally, it is hard to probe which mechanism is predominant, because one needs information about structural changes of the vortex lattice positional order as a function of time. Small angle neutron scattering (SANS) yields structural information along the field direction averaged over the sample volume, i.e., about the amount of entanglement of the VL.…”
mentioning
confidence: 99%